2017
DOI: 10.1002/adom.201600751
|View full text |Cite
|
Sign up to set email alerts
|

Protochromic Devices from a Cephalopod Structural Protein

Abstract: Cephalopods possess remarkable camouflage capabilities, which are enabled by their complex innervated skin architectures and advanced nervous systems. As such, cephalopod skin constitutes an exciting model for biomimetic camouflage technologies. This study draws inspiration from the constituent components of optically active ultrastructures found in squid skin cells to help design color‐changing bioelectronic devices, which consist of a proton‐transporting active layer contacted by a proton‐conducting actuatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 35 publications
0
34
0
1
Order By: Relevance
“…[124] Synthetic soft display and camouflage materials inspired by natural organisms,e specially those from animalia, have shown more capabilities than those found in nature.Recently, materials that demonstrate autonomous color-changing behaviors when triggered by multiple environmental stimuli have been developed. [125][126][127] Color or light, however, is not the only approach towards effective camouflage and stealth. Other aspects of visual perception may also affect ones ability to distinguish two entirely different objects.F or example,P ikul et al recently reported as tretchable membrane comprising af iber mesh embedded in as ilicone elastomer sheet.…”
Section: Soft Display and Camouflage Materialsmentioning
confidence: 99%
“…[124] Synthetic soft display and camouflage materials inspired by natural organisms,e specially those from animalia, have shown more capabilities than those found in nature.Recently, materials that demonstrate autonomous color-changing behaviors when triggered by multiple environmental stimuli have been developed. [125][126][127] Color or light, however, is not the only approach towards effective camouflage and stealth. Other aspects of visual perception may also affect ones ability to distinguish two entirely different objects.F or example,P ikul et al recently reported as tretchable membrane comprising af iber mesh embedded in as ilicone elastomer sheet.…”
Section: Soft Display and Camouflage Materialsmentioning
confidence: 99%
“…The gradual change of their optical or electrical properties in the presence of an external stimuli has been demonstrated to be very useful in neuromorphic systems . Recently, an organic‐based protein called reflectine, which is extracted from cephalopods, has been used to demonstrate color tuning in the visible, and camouflage in the visible to near‐IR ranges in mild environments when durability is not a critical factor …”
Section: Introductionmentioning
confidence: 99%
“…Inspiriert von natürlichen (insbesondere tierischen) Organismen haben synthetische weiche Anzeige‐ und Tarnmaterialien mehr Fähigkeiten als die natürlichen gezeigt. In den letzten Jahren wurden Materialien beschrieben, die ein autonomes Farbänderungsverhalten zeigen, das durch mehrere Stimuli aus der Umgebung ausgelöst wird . Farbe oder Licht ist jedoch nicht der einzige Ansatz zum wirksamen Tarnen.…”
Section: Weiche Materialienunclassified